Increasing the Capacity Building Program Based on Local Wisdom (Case study in Kepatihan Village, Gresik Regency) - Astuti, Sri Juni Woro; Endarti, Esa Wahyu; Mujiati, Mujiati; Andriyani, Nuraini Kusuma (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2021)
This study aims to describe village governance based on the principles of good governance and to reconstruct a more effective capacity building model based on local wisdom values. This study uses a mixed method of quantitative and qualitative methods. This research design intends to evaluate quantitative data and explore more deeply using qualitative data. The research sample consisted of 86 people taken from the population which included elements of the village apparatus, the Village Consultative Body and community leaders. Collecting data through questionnaires, interviews and secondary data. Data analysis, firstly carried out descriptively quantitative then elaborated with interactive qualitative data. The results showed that the Kepatihan village government had not met the criteria for good governance. This is partly due to the ineffective capacity building program. The suggestion of this research is that there is a need for a more effective approach by synergizing with local wisdom values so that the capacity building program can truly internalize and ultimately increase the competence of village officials. The novelty presented from this research is to increase the effectiveness of the village apparatus capacity building program, which can be synergized with local village traditional events.